ANALISIS SPASIAL KONVERSI HABITAT BABIRUSA (BABYROUSA CELEBENSIS) MENJADI LAHAN PERTANIAN DAN PERKEBUNAN DI PROVINSI GORONTALO - Ahmad Zainuri; Dewi Wahyuni K Baderan; Marini Susanti Hamidun; Iswan Dunggio; Sukirman Rahim; Daud Yusuf (LPPM Universitas Cipta Mandiri, 2024)
This study used ArcGIS computer tools, GPS and digital cameras for field data collection and documentation. The main data included Babirusa habitat maps from the IUCN, land cover maps and supporting field data. Independent variables were changes in Babirusa habitat, while dependent variables included habitat extent and quality. Spatial data was downloaded from sources such as the Geospatial Information Agency, IUCN and the Ministry of Forestry's Pusdatin, and analysed with ArcGIS, while non-spatial data from field research was analysed statistically and qualitatively. Four main analysis methods were used to understand the impact of land cover change on Babirusa habitat, including overlay analysis to highlight areas of intensive impact and change. IUCN 2021 data shows that Babirusa habitat in Gorontalo covers approximately 993,971.08 hectares. Of this area, 124,887.63 hectares or 20.93% has been converted to agricultural land, and 29,051.4 hectares or 2.92% to plantation land.